The genome sequence of Vibrio parahaemolyticus C5A causing acute hepatopancreatic necrosis disease in shrimps isolated from a Malaysia shrimp culture pond - Amatul-Samahah, Md. Ali; Muthukrishnan, Sarmila; Al-saari, Nurhidayu; Mohd Ikhsan, Natrah Fatin; Saad, Mohd Zamri; Azmai, Mohamad Noor Amal; Yusof, Mohd Termizi; Md Yasin, Ina-Salwany; Tanaka, Mami; Mino, Sayaka; Sawabe, Tomoo (Elsevier, 2022)
We report the complete genome sequence of Vibrio parahaemolyticus strain C5A causing an acute hepatopancreatic necrosis disease (AHPND) in Penaeus vannamei sampled from a culture pond in the east of peninsular Malaysia isolated in 2017.